The Students Thinking Process in Constructing Evidence with Mathematics Induction Reviewed from Information Processing Theory - Buhaerah Buhaerah; Muhammad Nasir; Kamarrussama Jusoff (Universitas Muhammadiyah Mataram, 2022)
This study describes the student's thought process in constructing evidence that begins with a stimulus. The stimulus is then entered into the sensory register through the senses of sight and hearing. The attention that occurs is focused on the complete problem as indicated by the emergence of perceptions about stimuli following the information given, namely solving the problem by mathematical induction. In short-term memory, the construction of proofs by mathematical induction begins in retrieving the concepts of mathematical induction principles. The research subjects were six students of Tadris Mathematics; namely, two people with high abilities or the upper group, two people with low skills or the lower group, and two people with medium abilities or the middle group. The retrieval process in students belonging to the upper group runs smoothly. In the long-term memory of the issues of this group, the knowledge needed by working memory is stored. Proof of truth by mathematical induction is interpreted correctly, proving the truth for n=1 to n=k+1. The assumption of truth for n=k is the basis for establishing the truth for n=k+1 by upper group subjects. This is different from what happened to the topics of the middle and lower groups. The assumption of truth for the written value of n=k is not involved in proving the truth for n=k+1. The encoding process that occurs in students is in the form of strengthening some concepts that have been retrieved from long-term memory.